2018
DOI: 10.1080/00207543.2018.1521025
|View full text |Cite
|
Sign up to set email alerts
|

Low-Certainty-Need (LCN) supply chains: a new perspective in managing disruption risks and resilience

Abstract: This study suggests a new approach to supply chain (SC) disruption risk management where SC behaviour is less dependent on the certainty of our knowledge about the environment and its changes. The unpredictability of the occurrence of disruption and its magnitude suggests that designing SCs with a low need for 'certainty' may be as important, if not more so, than predetermined disruption control strategies. In this setting, this study calls for the development of a new perspective in SC disruption management, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
93
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 248 publications
(99 citation statements)
references
References 149 publications
0
93
0
Order By: Relevance
“…Second, despite the interrelations between operational resilience, disruption, and efficiency Wong et al, 2019), empirical knowledge of their interplay remains underdeveloped. Whereas some authors express doubt about the efficiency value of resilience (e.g., van der Vegt et al, 2015), Ivanov and Dolgui (2019) propose the idea of low-certainty-need to suggest that resilience and efficiency can coexist when resilience-building behavior is less dependent on certainty of knowledge about the occurrence and impacts of disruptions. Subsequently, Wong et al (2019) investigate the complexities associated with these variables by linking resilience to financial performance.…”
Section: Introductionmentioning
confidence: 99%
“…Second, despite the interrelations between operational resilience, disruption, and efficiency Wong et al, 2019), empirical knowledge of their interplay remains underdeveloped. Whereas some authors express doubt about the efficiency value of resilience (e.g., van der Vegt et al, 2015), Ivanov and Dolgui (2019) propose the idea of low-certainty-need to suggest that resilience and efficiency can coexist when resilience-building behavior is less dependent on certainty of knowledge about the occurrence and impacts of disruptions. Subsequently, Wong et al (2019) investigate the complexities associated with these variables by linking resilience to financial performance.…”
Section: Introductionmentioning
confidence: 99%
“…Practices for managing SCRs can be categorized as SC resilience, SC agility, and SC robustness [20][21][22][23]. The previous literature suggests that these three practices are followed when SCR mitigation strategies are developed [3,20,[24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Although the previous literature suggests the importance of SC resilience, SC agility, and SC robustness for managing SCRs [8,28,36], it has surprisingly treated them separately and lacks in clarifying their context to different situations and applicability. The previous literature is insufficient in explaining which practice to use in handling which type of risk.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers (Allesina, Azzi, Battini, & Regattieri, 2010;Ivanov & Dolgui, 2018) and policy advisers argue that networks of interconnected firms play a pivotal role in equipping firms with a competitive advantage. Therefore, entrepreneurs are looking toward their ecosystem in order to achieve success for themselves.…”
Section: Entrepreneurial Ecosystem: Definitions and Dimensionsmentioning
confidence: 99%
“…Hence, entrepreneurial decisions are inevitably dependent on how individuals judge their entrepreneurial ecosystem. Although previous studies have shown a positive effect on fundamental decisions in the context of founding a new venture (e.g., Ivanov & Dolgui, 2018;Suresh & Ramraj, 2012), research exists on the prioritization of individual components of EES. It is essential to analyze the relative contribution of these factors in order to devise the optimal entrepreneurial promotion policy.…”
Section: Introductionmentioning
confidence: 99%